DAUR ULANG DAN PENGGUNAAN KEMBALI SAMPAH MENGGUNAKAN INSINERATOR DI SIDODADI NGANTANG - Achmad Safi; Slamet Wibawanto; Ira Kumalasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract Rural development in Indonesia requires planning and participation from various parties, including universities, one of which is the State University of Malang. UM has collaborated in the field of Community Service (PKM) to build villages through the LP2M Institution to spur quality improvement and village development. Important points that become indicators of village development are related to community empowerment and village economic resilience. One of UM's fostered villages is Sidodadi Village, Ngantang District, Malang Regency. Based on the results of a preliminary study related to the situation analysis carried out in direct coordination with the Village Head, that the village is working on the construction of a Final Disposal Site (TPA). In the process of development and construction, the shortage that is being experienced is the absence of incinerators and plastic waste processors. Through PKM, this activity seeks to provide products in the form of an incinerator to melt plastic waste, then the fused product is used as a paving material. The proposed activity plan consists of several stages, namely: 1) literature study stage; 2) stages of data collection; 3) stages of system planning; 4) stages of system creation and testing; 5) stages of system revision; and 6) stages of product delivery and socialization. The result of this service is an incinerator that can process plastic waste into paving and provides training to TPA managers on how to use incinerators and their treatments. Abstrak Pembangunan Desa di Indonesia memerlukan perencanaan dan partisipatif dari berbagai pihak, termasuk perguruan tinggi, salah satunya Universitas Negeri Malang. UM telah menjalin kerja sama di bidang Pengabdian Kepada Masyarakat (PKM) bangun Desa melalui Lembaga LP2M untuk memacu peningkatan kualitas dan mutu pembangunan Desa. Poin penting yang menjadi indikator pembangunan Desa, yaitu terkait pemberdayaan masyarakat dan ketahanan ekonomi Desa. Salah satu Desa Binaan UM adalah Desa Sidodadi, Kecamatan Ngantang, Kabupaten Malang. Berdasarkan hasil studi pendahuluan terkait analisis situasi yang dilakukan dengan berkoordinasi secara langsung bersama Kepala Desa, bahwa Desa sedang mengupayakan pembangunan Tempat Pembuangan Akhir (TPA). Dalam proses pengembangan dan pembangunannya, kekurangan yang tengah dialami adalah belum adanya insinerator dan pengolah sampah plastik. Melalui PKM, kegiatan ini berupaya untuk memberikan produk berupa alat insinerator pelebur sampah plastik, kemudian hasil leburannya digunakan sebagai bahan pembuatan paving. Rencana kegiatan yang diusulkan terdiri dari beberapa tahapan yaitu: 1) tahapan studi literatur; 2) tahapan pengumpulan data; 3) tahapan perencanaan sistem; 4) tahapan pembuatan dan uji coba sistem; 5) tahapan revisi sistem; dan 6) tahapan penyerahan dan sosialisasi produk. Hasil dari pengabdian ini adalah alat insinerator yang dapat mengolah limbah plastik menjadi paving dan pemberian pelatihan pada pengelola TPA cara menggunakan alat insinerator serta perawatannya.